Comparison between the efficacy of switch therapy and conventional therapy in pediatric community-acquired pneumonia - Supinya In-Iw (2018)
© 2015, Medical Association of Thailand. All Rights reserved. Objective: Compare the treatment outcomes of switch therapy and conventional therapy in pediatric patients aged one month to five years old, diagnosed with community-acquired pneumonia who required hospitalization. Material and Method: The present study was performed and approved by the Siriraj Research Ethics Committee. With informed consent, 57 patients who fitted the inclusion criteria were randomized into two groups, 1) the switch therapy group (SWT), who switched their method of receiving antibiotics from IV to oral within 24 hours after clinical improvement and body temperature under 37.8°C at least eight hours, and 2) the control group, the group treated as routine general practice. Chi-square tests, Fisher’s exact tests, unpaired t-tests, and Mann-Whitney U tests were used in analysis. A non-inferiority analysis to estimate 1-sided 95% CIs was performed to determine the greatest difference (worst case) between groups. Results: There were no significant differences in age, sex, clinical presentations, and antibiotics provided between the two groups. A statistically significant reduction in length of hospital stay was found in the SWT group (p = 0.019), whereas the readmission rate for both groups was not significantly different (p = 0.66). Morbidity and mortality were not found in either groups. The SWT group demonstrated non-inferior efficacy comparing to control group (difference 20%; p<0.001). Conclusion: In pediatric community-acquired pneumonia, early switching from administer IV antimicrobial agents to oral form when clinical signs improved were safe and effective. Switch therapy showed non-inferiority outcomes compared to conventional therapy, and had advantages in shortening the length of stay and indirectly lowering the cost of hospitalization.